PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN IPS TERPADU SISWA KELAS VII B SEMESTER GENAP DI SMP IT FATWAH JANGKAR PADA TAHUN PELAJARAN 2017/2018 - Rendy Yogi Septiawan; Dassucik Dassucik (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
In developing quality human resources in integrated social studies subjects, there are several difficulties for students, including: low student ability in understanding integrated social studies subjects as well as, ineffective learning methods, monotonous from time to time, authoritarian teachers. and less friendly to students, a poor evaluation tool. So that students feel bored and have less interest in learning. Based on the observations of SMP IT Fatwah Jangkar, when the teacher gave lessons to students, he found several problems in the social studies / economics learning process. There are some students who lack concentration when learning takes place. This is possible because learning takes place in a monotone so that students are less motivated to learn. This type of research is classroom action research. Collecting data in this study using the method of observation, documentation, interviews, and tests. The results of this study indicate that the application of learning with the Problem Based learning model can be used as an alternative in social studies learning. Social studies learning using the Problem Based Learning learning model has a positive impact on student involvement in learning activities which can be seen from the very good percentage of student activity. The results also showed that the students' learning outcomes were classically complete, that is, more than 80% of the students had successfully studied individually.